Literature Study of Halal UMKM Industry Development Model in Trang, Southern Thailand: English - Sohibul Wafa Fadlan Zamil; Rahmayati (Muhasabatuna : Jurnal Akuntansi Syariah, 2023)
The development of the halal industry sector will continue to compete again with the involvement of the Islamic banking and Islamic finance sectors. This study aims to examine the roles of the Islamic banking and Islamic finance sectors in developing halal food and SMEs in Trang, southern Thailand. This study uses a descriptive qualitative approach to literature studies. Based on the results of the research, it can be seen that Islamic banking has a role not only in financing that is free from usury or interest, gambling and uncertainty, but also in all stages of the halal value chain or stages of the production process. Islamic banking has an important role in developing and improving the halal food industry sector which goes through three stages of halal integrity. The first stage is the halal process, the second is logistics and the third is halal verification.